IMPLEMENTASI PEMBELAJARAN PENDIDIKAN ANTIKORUPSI UNTUK MENINGKATKAN INTEGRITAS SISWA: STUDI KASUS DI SEKOLAH MENENGAH KEJURUAN - Susanti, Septiani Selly; Salsabila, Hawa Failasifa; Asy'arie, Bima Fandi (LPPM STAI DARUSSALAM LAMPUNG, 2025)
Abstract: Anti-corruption education is one of the important efforts to equip students with a deep understanding of corruption, its negative impacts, and the importance of integrity. Anti-corruption education forms moral character, teaches honest actions, and helps build a generation that plays a role in preventing and reducing the level of corruption in society. The study aimed to determine the implementation of anti-corruption education learning and the supporting and inhibiting factors in the implementation of student integrity learning. This type of research is a case study with a qualitative approach. This research was conducted at SMK Darul Amal, Metro City, Lampung. The data collection techniques used were interviews, observation, and documentation. The analysis model used was data reduction, data presentation, and concluding. The study's results were to determine the implementation of anti-corruption education learning in determining learning steps, learning objectives using learning methods and media, evaluating learning that had been implemented, and analyzing inhibiting and supporting factors of anti-corruption education teaching to improve student integrity. Keywords: implementation, learning, anti-corruption education, student integrity.